Empirical Evidence on Growth Spillovers from China to New Zealand - Denise R Osborn; Tugrul Vehbi (New Zealand Government, The Treasury, 2013)
This paper provides a quantitative analysis of the impact on New Zealand of economic growth in China through the framework of an econometric model. The analysis compares the roles of China and the US both for growth in New Zealand and also for world commodity prices, the latter being important for New Zealand as an exporter of primary products. Finally, in the light of the increasing role of China in the world economy over the last two to three decades, the paper also investigates whether spillover effects from China to New Zealand have changed over this period. Using models estimated from the mid- 1980s to 2011, we find that growth spillovers from China are important for New Zealand, with estimates of the accumulated increase in domestic GDP from a one percent increase in output growth in China being in the range of around 0.2 to 0.4 percent. It is striking that growth spillovers are substantially greater from the US than from China, despite the latter's increasing importance in the world economy. Both domestic and foreign shocks have been important drivers of real exchange rate fluctuations, while the contribution of the latter has been relatively more important. The time-varying estimates provide some evidence of time-variation, with the greatest impact from China applying for about a decade from the mid-1990s, but also being relatively large in the latter part of our sample period.
Keywords: 330; C32; E32; F43; F44